Origin of optoelectronic contradictions in 3,4-cycloalkyl[c]-chalcogenophenes: a computational study - Masilamani, Ganesh; Krishna, Gamidi Rama; Debnath, Sashi; Bedi, Anjan (Polymers, 2023)
The planar morphology of the backbone significantly contributes to the subtle optoelectronic features of pi-conjugated polymers. On the other hand, the atomistic tuning of an otherwise identical pi-backbone could also impact optoelectronic properties systematically. In this manuscript, we compare a series of 3,4-cycloalkylchalcogenophenes by tuning them atomistically using group-16 elements. Additionally, the effect of systematically extending these building blocks in the form of oligomers and polymers is studied. The size of the 3,4-substitution affected the morphology of the oligomers. In addition, the heteroatoms contributed to a further alteration in their geometry and resultant optoelectronic properties. The chalcogenophenes, containing smaller 3,4-cycloalkanes, resulted in lower bandgap oligomers or polymers compared to those with larger 3,4-cycloalkanes. Natural bonding orbital (NBO) calculations were performed to understand the disparity alongside the contour maps of frontier molecular orbitals (FMO).
Keywords: chalcogenophene; DFT calculation; Morphology; optoelectronic properties; steric effect